Arthropod pests of kiwifruit identified from Chinese language literature - Xu, Bingqin; Teulon, David A.J. (New Zealand Plant Protection, 2019)
References to many other kiwifruit arthropod pests (and diseases) were found as part of a process of searching Chinese language literature to understand the impact of brown marmorated stink bug (Halyomorpha halys; BMSB) and spotted lantern fly (Lycorma delicatula; SLF) on kiwifruit (Actinidia chinensis) and A. deliciosa in China. Information on other kiwifruit pests was collated from over 20 Chinese language publications found in searches of the Chinese National Knowledge Infrastructure platform using standard Chinese characters for BMSB, SLF and kiwifruit, and was ranked according to: (1) the number of publications they were mentioned in; and (2) the type of words used to describe their impact. In addition to BMSB and SLF, approximately 50 kiwifruit pests were identified from this process, including a number of species that were unknown to the New Zealand kiwifruit biosecurity community and which may pose a threat to kiwifruit production if they established in New Zealand. This work reinforces the need for searching Chinese databases with Chinese characters in combination with searches in international databases, to ensure comprehensive coverage for biosecurity risk assessment.